2011
DOI: 10.1088/0957-4484/22/27/275702
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer and partial pinning at the contacts as the origin of a double dip in the transfer characteristics of graphene-based field-effect transistors

Abstract: We discuss the origin of an additional dip other than the charge neutrality point observed in the transfer characteristics of graphene-based field-effect transistors with a Si/SiO2 substrate used as the back-gate. The double dip is proved to arise from charge transfer between the graphene and the metal electrodes, while charge storage at the graphene/SiO2 interface can make it more evident. Considering a different Fermi energy from the neutrality point along the channel and partial charge pinning at the contac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 38 publications
(83 reference statements)
6
85
0
Order By: Relevance
“…If the Fermi level is not pinned, the gate voltage is able to further tune the charge density of graphene in the contact region [53][54]. [43].…”
Section: Resultsmentioning
confidence: 99%
“…If the Fermi level is not pinned, the gate voltage is able to further tune the charge density of graphene in the contact region [53][54]. [43].…”
Section: Resultsmentioning
confidence: 99%
“…A positive charge that is trapped at the graphene/oxide interface in the vicinity of the drain has induced the formation of a p-n junction in the drain region resulting in sharp and distinct Dirac points. [ 11,18 ] [ 57 ] A second feature observed in their I d -V gs curves is a clear hysteresis between the forward and reverse sweeps of the gate voltage. In this work, we deposited an ultrathin layer of PEIE (10 nm thick) and observed two distinct Dirac points without any appearance of hysteresis or a need for electrical cycling.…”
Section: Electrical Data Measurementsmentioning
confidence: 99%
“…Antonio et al [70] ascribed double dip in I ds − V bg to charge transfer between the graphene and the metal electrodes. Nouchi et al [71] have also reported that anomalously distorted transportation originated from the partially formed oxide layer in Ni/graphene contact.…”
Section: Interface Impactmentioning
confidence: 99%